(untitled) (Baghdad Science Journal, 2025)
A numerical investigation has been performed to examine the effect of fluorine concentration on the chain reaction mechanisms and parameters of hydrogen fluoride (HF) chemical laser. The practical difficulties associated with this type of lasers impose that an alternative route might be quite useful. Thus, particular attention was paid to develop a computer program to investigate various processes. The results of this computer simulation program proved their credibility when compared with the little published data. This computer program is called Reaction Rate Simulation Model (RRSM). An entirely new approach to emulate the reaction mechanisms has been followed. The effectiveness of reaction rates in the processes of HF laser production has been investigated. This simulation program dealt with the percentages of the forward and reverse reactions, when a large number of reactions have been considered. In addition a large number of species have been taken into account in these reactions. From the computer program (RRSM), some valuable results could be predicted with regard to the hydrogen fluoride chemical laser.